2005
DOI: 10.3133/sir20045301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alternative instream-flow criteria and water-supply demands on ground-water development options in the Big River Area, Rhode Island

Abstract: Daily streamflow-duration curves showing the percentage of time that the estimated streamflow would be equaled or exceeded in four different groundwater withdrawal scenarios for the A, Lake Mishnock Outflow (station 01115965); B, Mishnock River at State Route 3 (station 01115970); C, Carr River below Capwell Mill Pond (station 01115770); and D, Big River at Hill Farm Road

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(64 citation statements)
references
References 10 publications
2
57
0
Order By: Relevance
“…Other than the hypothetical pumping well, all simulation inputs, including all wells, were the same as those of the baseline simulation. Granato and Barlow, 2005 Because the simulation response to the pumping rate of a well is nearly linear in most parts of the study area, the predicted depletion generally is not sensitive to the pumping rate selected for the hypothetical well; however, the sensitivity of predicted depletion to pumping rate was tested for this simulation. Alternative pumping (water removed from the aquifer) rates of 10, 1.0, and 0.1 ft 3 /s and injection (water pumped into the aquifer) rates of 0.1, 1.0, and 10 ft 3 /s were tested for the hypothetical well.…”
Section: Base-flow Depletion Percentage For a 50-year Periodmentioning
confidence: 99%
“…Other than the hypothetical pumping well, all simulation inputs, including all wells, were the same as those of the baseline simulation. Granato and Barlow, 2005 Because the simulation response to the pumping rate of a well is nearly linear in most parts of the study area, the predicted depletion generally is not sensitive to the pumping rate selected for the hypothetical well; however, the sensitivity of predicted depletion to pumping rate was tested for this simulation. Alternative pumping (water removed from the aquifer) rates of 10, 1.0, and 0.1 ft 3 /s and injection (water pumped into the aquifer) rates of 0.1, 1.0, and 10 ft 3 /s were tested for the hypothetical well.…”
Section: Base-flow Depletion Percentage For a 50-year Periodmentioning
confidence: 99%
“…For example, Granato and Barlow (2005) and Granato and Walter (2011) used retrospective streamflow-depletion analyses to demonstrate the potential effects of applying different conjunctive water-withdrawal management plans to the historical record of streamflows at different sites of interest.…”
Section: Retrospective Streamflow-depletion Analysismentioning
confidence: 99%
“…This approach, however, has evolved into a sustainable yield approach that includes streamflow-maintenance objectives to approximate natural flows for the entire flow-duration curve (Poff and others, 1997;Sophocleous, 2000;Alley and Leake, 2004;Maimone, 2004;Archfield and others, 2010). For groundwater supplies, however, Granato and Barlow (2005) and Granato and Walter (2011) demonstrated that the nature of streamflow depletions caused by groundwater withdrawals, the annual cycle of water-use patterns, and the annual variations in streamflows in this region make it feasible for properly managed allowable-depletion objectives to be used to meet sustainable yield objectives for groundwater supplies in alluvial-valley aquifers that are in direct hydraulic connection with rivers, brooks, and streams in the northeastern United States.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations